Novel potential metabolic enzymes inhibitor, photosensitizer and antibacterial agents based on water-soluble phthalocyanine bearing imidazole derivative - Gunsel, Armagan; Taslimi, Parham; Atmaca, Goknur Yasta; Bilgicli, Ahmet T.; Piskin, Hasan; Ceylan, Yusuf; Erdogmus, Ali; Yarasir, M. Nilufer; Gulcin, Ilhami (ELSEVIER, 2021)
In this work, we have reported on the synthesis and characterization of water-soluble hydrochloride forms (2a-4a) based on novel peripherally [M = metal-free (2), zinc (II) (3), gallium (III) chloride (4)] phthalocyanines bearing 1-methyl-H-1-imidazole-2-thiol substituents. Characterization of all compounds used was supported by a series of spectroscopic techniques such as UV-Vis, FT-IR H-1 NMR, C-13 NMR and MALDI-MS, etc. The confirmation of the molecular structure of 4-(1-methyl-H-1-imidazole-2-thiol) phthalonitrile (1) by single crystal x-ray diffraction experiment was performed for the first time in this work. Besides, the intra/inter-molecular interactions inside the obtained crystal structure have been investigated. Afterward, the effects of the central metal atoms and solvents on the photophysicochemical properties of the phthalocyanines were analyzed to investigate their potential to use as a photosensitizer in photodynamic theraphy (PDT). The obtained results show that the phthalocyanines have therapeutic outcomes for cancer treatment. It has been seen that all compounds have a better ability to inhibit compared to existing tried inhibitors. Among these, the best inhibitors against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzymes are (4) (Ki 47.71 +/- 9.14 mu M and IC50 68.22) and (3a) (Ki 20.12 +/- 3.75 mu M and IC50 19.24), respectively. Also, against alpha-Glycosidase, (4) showed the highest effect (Ki 9.13 +/- 1.05 mu M and IC50 11.22). Phthalocyanines were performed to gram-negative and gram-positive bacteria using minimum inhibition concentration (MIC) assay and indicated an antibacterial effect. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Synthesis, crystal structure, antibacterial; Enzyme inhibition; DISUBSTITUTED SILICON PHTHALOCYANINES; IN-VITRO; PHOTOPHYSICOCHEMICAL PROPERTIES; ELECTROCHEMICAL PROPERTIES; STRUCTURE VALIDATION; DNA PHOTOCLEAVAGE; DNA/BSA BINDING; GALLIUM(III); INDIUM(III); Chemistry